Dangerous pumpkins - Jenkins, Emily, 1967- (Invisible Inkling, 2012)
Halloween brings out the worst in fourth-grader Henry Wolowitz and his invisible, squash-eating friend Inkling, as Henry tries to go trick-or-treating while keeping Inkling from eating all the jack-o-lanterns.